2017
DOI: 10.11604/pamj.2017.27.199.11066
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of high-energy pilon fractures using the ILIZAROV treatment

Abstract: The management of high-energy pilon fractures is still controversial. Open reduction and internal fixation are often associated with serious complications. Various methods have been used to treat these injuries, with variable results. The aim of this retrospective study was to analyze the clinical and radiographic outcome of the ILIZAROV technique in patients with high-energy pilon fractures. Thirty cases of distal tibia epiphysis fractures (pilon fractures) were managed from 1999 to 2012. The study group incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 15 publications
(27 reference statements)
4
29
0
Order By: Relevance
“…In the present study, we used monolateral external fixator for complex tibial pilon fractures as definitive treatment, which allowed fracture union with functional mobility. The average time to union was of 14 weeks which was comparable to studies by Mitkovic et al and Osman et al 19,3 However other factors like open fracture at the time of injury, post-operative infections, smoking habits, and others, do affect the time to union.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, we used monolateral external fixator for complex tibial pilon fractures as definitive treatment, which allowed fracture union with functional mobility. The average time to union was of 14 weeks which was comparable to studies by Mitkovic et al and Osman et al 19,3 However other factors like open fracture at the time of injury, post-operative infections, smoking habits, and others, do affect the time to union.…”
Section: Discussionsupporting
confidence: 83%
“…However, the optimal solution has not been determined [40][41][42][43]. Previous research indicates 6 BioMed Research International that olive wires could also offer enough compression to maintain the fracture's stability [44][45][46]. The threaded part of the pin utilized for medial malleolus fixation in this study increased the friction to the bone, which composed a stronger fixation with the combination of compression offered by olive wire.…”
Section: Medial Malleolus Fixationmentioning
confidence: 88%
“…Although there are few studies that have reported the joint reduction quality following surgery of highenergy pilon fractures, in a study of 30 patients treated with Ilizarov external fixator, Osman et al [17] reported that acceptable reduction was obtained in 46.6% and poor reduction in 20%. In another study of 17 patients, Kapoor et al [13] reported that in 4 patients with AO-43C3 type open tibial pilon fractures, acceptable joint reduction was obtained with Ilizarov external fixator passing the joint.…”
Section: Discussionmentioning
confidence: 99%
“…In 30 patients with high-energy tibialpilon fractures treated with Ilizarov external fixator by Osman et al [17], arthrosis developed in the joint in 11 patients, but no information was given about the grade of arthrosis. Fırat et al [23] compared the Ilizarov external fixator techniques of fixed to the ankle and jointed at the ankle in 34 patients operated on for tibial pilon fracture.…”
Section: Discussionmentioning
confidence: 99%